SOCIALIZATION OF OCCUPATIONAL SAFETY PROTECTION IN ASAM KUMBANG VILLAGE. MEDAN CITY - M. Citra Ramadhan; Rudi Salam Sinaga; Taufik Siregar (LEMBAGA KAJIAN ILMU SOSIAL DAN POLITIK (LKISPOL), 2021)
Work safety is an important concern in achieving the goals of work activities. This activity aims to provide workers with an understanding of the laws relating to work safety. The method of activity is carried out in the form of socialization and discussion. Participants in the activity came from various elements of workers who live in the work area in the Asam Kumbang village. This activity was carried out in the Asam Kumbang village in the city of Medan. To be able to find out the response and knowledge of the activity participants who came from workers on work safety, a question and answer session was held. The results of the activities that have been carried out have increased the understanding of work safety for participants